The Moderating Role of Locus of Control in the Effect of Self-Efficacy on Academic Resilience - Prawitasari, Tiara; Sugiyo, Sugiyo; Saraswati, Sinta (Universitas Negeri Semarang, 2023)
Academic resilience is important to enhance students in achieving good academic performance in the learning process. The lack of it may affect students’ adaptability, while its underlying factors are such as self-efficacy and locus of control. Regarding this issue, the present study attempted to analy zed the role of locus of control in moderating the effect of self-efficacy on the academic resilience of eight graders all over Kendal Regency. It was quantitative research that surveyed 202 students as the respondents using an instrument developed based on Cassidy’s academic resilience scale (2016), Bandura’s self-efficacy (1997), and Levenson’s locus of control scale (1981). The collected data were examined using the Hayes model 1 moderation test. Findings indicated that self-efficacy had no effect on academic resilience, but locus of control on internality scores provided a moderating effect that strengthened the effect of self-efficacy on academic resilience. In addition, locus of control on powerful other and chance scores had no moderating effect. Thus, further studies are suggested to deepen the examination of the effect of internal locus of control on academic resilience.